2007
DOI: 10.1111/j.1600-065x.2007.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

How human neutrophils kill and degrade microbes: an integrated view

Abstract: Neutrophils constitute the dominant cell in the circulation that mediates the earliest innate immune human responses to infection. The morbidity and mortality from infection rise dramatically in patients with quantitative or qualitative neutrophil defects, providing clinical confirmation of the important role of normal neutrophils for human health. Neutrophil-dependent anti-microbial activity against ingested microbes represents the collaboration of multiple agents, including those prefabricated during granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
574
2
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(591 citation statements)
references
References 189 publications
5
574
2
10
Order By: Relevance
“…Detailed reviews of neutrophil killing functions can be found elsewhere. 7 Given this arsenal of destructive power, it is remarkable that recruited neutrophils can efficiently enter tissues and destroy invading pathogens (a process culminating in the resolution of infection/inflammation), usually with little residual tissue damage. In addition, it is well documented that infiltration of inflammatory cells, including neutrophils, macrophages, and lymphocytes, is necessary for the process of mucosal wound healing.…”
Section: Other Subsets Of Neutrophil Granules Contain Lactoferrinmentioning
confidence: 99%
“…Detailed reviews of neutrophil killing functions can be found elsewhere. 7 Given this arsenal of destructive power, it is remarkable that recruited neutrophils can efficiently enter tissues and destroy invading pathogens (a process culminating in the resolution of infection/inflammation), usually with little residual tissue damage. In addition, it is well documented that infiltration of inflammatory cells, including neutrophils, macrophages, and lymphocytes, is necessary for the process of mucosal wound healing.…”
Section: Other Subsets Of Neutrophil Granules Contain Lactoferrinmentioning
confidence: 99%
“…Killing and degradation of the microorganism proceed in the small phagosomal space in a concentrated action of the involved ingredients, although the contribution of the individual factors may vary depending on the type of microorganism [89,91]. The molecular details of these processes have been worked out and summarized in recent excellent reviews [11,58,66,75,77,78,80,102,115].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly the prototype agonist formylmethionyl-leucyl-phenylalanine (fMLF) is a bacterial produced high-affinity FPR1 agonist that triggers a variety of biologic activities in neutrophils, including chemotaxis, granule secretion, cytokine production, and superoxide release, the latter generated through an activation of an electron transporting NADPH-oxidase [6]. The reactive oxygen species (ROS) derived from the activated NADPH-oxidase are essential for a successful clearance of bacteria during infection as illustrated by the fact that patients lacking a functional oxidase suffer repeatedly from severe bacterial infections [7]. In addition to FPR1, neutrophils express also a closely related receptor, FPR2, that belongs to the same receptor family [4,5].…”
Section: Introductionmentioning
confidence: 99%